2019
DOI: 10.1007/s00280-019-03843-0
|View full text |Cite
|
Sign up to set email alerts
|

A single-arm phase II trial of weekly nanoparticle albumin-bound paclitaxel (nab-paclitaxel) monotherapy after standard of chemotherapy for previously treated advanced non-small cell lung cancer

Abstract: Background Few studies have investigated the clinical efficacy of third- and later-line of chemotherapy after standard chemotherapy for previously treated advanced non-small cell lung cancer (NSCLC). We prospectively evaluated the efficacy and safety of nanoparticle albumin-bound paclitaxel (nab-paclitaxel) following standard chemotherapies for previously treated advanced NSCLC. Methods The eligible patients having adequate organ functions with performance status 0–2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In a previous review article, sb-PTX therapy was associated with a higher incidence of grade ≥3 peripheral neuropathy compared to nab-PTX therapy (9). However, we compared our study results and sb-PTX monotherapy results (3,6,(14)(15)(16)(17)(18)(19), and we could not detect the clinical benefit of nab-PTX in peripheral neuropathy. This was perhaps because our study included two patients who had previously been treated with sb-PTX and/or 11 heavily treated patients who were treated with three or more previous regimens.…”
Section: Discussionmentioning
confidence: 76%
“…In a previous review article, sb-PTX therapy was associated with a higher incidence of grade ≥3 peripheral neuropathy compared to nab-PTX therapy (9). However, we compared our study results and sb-PTX monotherapy results (3,6,(14)(15)(16)(17)(18)(19), and we could not detect the clinical benefit of nab-PTX in peripheral neuropathy. This was perhaps because our study included two patients who had previously been treated with sb-PTX and/or 11 heavily treated patients who were treated with three or more previous regimens.…”
Section: Discussionmentioning
confidence: 76%
“…In the phase I/II trial of weekly nab-PTX as the firstline chemotherapy in stage IV NSCLC patients treated with 125 mg/m 2 of nab-PTX on days 1, 8, and 15 on a 28day cycle, the most common grade 3/4 adverse events were neutropenia (20%), leukopenia (20%), fatigue (18%), and peripheral sensory neuropathy (15%) [7]. In previous studies of weekly nab-PTX for pretreated NSCLC, the incidence of toxicities was neutropenia (19.5-38.6%), leukopenia (17.1-25%), fatigue (0-23%), peripheral sensory neuropathy (1.8-9.6%), and febrile neutropenia (0-12.9%) [23][24][25][26][27]. Although the incidence of neutropenia and leukopenia of grade 3/4 was high in the present study, febrile neutropenia was not observed.…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…Some earlier prospective studies of secondor later-line nab-PTX for NSCLC were reported. Two prospective studies of a 3-week cycle treatment (days 1, 8, and 15) of 100 mg/m 2 nab-PTX as a later-line therapy reported an ORR of 22.7-31.7%, DCR of 65.9-81.8%, median PFS of 3.4-4.9 months, and median OS of 7.4-13 months [23,24]. In 3 prospective studies of a 4-week cycle treatment (days 1, 8, and 15) of 100 mg/m 2 nab-PTX as a later-line therapy, the ORR was 7.3-28.1%, the DCR was 54.5-74.1%, the median PFS was 3.4-4.5 months, and the median OS was 10.6-15.7 months [25][26][27] ( Table 4).…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy is widely applied for treatment of multiple cancer types, with one or more anticancer drugs generally used as part of a standardized chemotherapy regimen in the clinic ( Johnstone et al, 2002 ). However, chemotherapy drugs often have poor targeting problems, and combined application of several drugs inevitably results in a series of adverse events ( Sarah, 2013 ), such as bone marrow dysfunction, peripheral neuropathy, chronic pain, sleep disorders, nausea and vomiting, fatigue, and flushes, which not only negatively affect curative effects but also lead to severe patients’ discomfort and poor quality of life (QOL) posttreatment ( Torre et al, 2015 ; Kato et al, 2019 ; Makary et al, 2019 ). Bone marrow suppression remains a major toxic effect ( Yeshurun et al, 2014 ), which is characterized by a decrease in three critical cell types: leukocytes, erythrocytes, and platelets.…”
Section: Introductionmentioning
confidence: 99%